Performing Exile, Performing Self - Meerzon, Y. author. aut Link
XI, 350 p.
Keywords: This book examines the life and art of those contemporary artists who by force or by choice find themselves on other shores. It argues that the exilic challenge enables the émigré artist to (re)establish new artistic devices, new laws and a new language of communication in both his everyday life and his artistic work.